Application Of Back Massage To Smooth Milk In Breastfeeding Mothers At Pelamonia Makassar Hospital - Erna Kasim; Sri Ayun Kum; Andi Tenriola Fitri Kessi (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2022)
ABSTRACT Introduction: The action of rolling massage (back) can affect the hormone prolactin which functions as a stimulus for breast milk production in mothers during breastfeeding. The action of massage rolling (back) will provide comfort and relax the mother because massage rolling can stimulate the release of endorphins and can stimulate the oxytocin reflex. The purpose of the study: to identify how to apply back massage (massage rolling) to facilitate breastfeeding in breastfeeding mothers. Methods: In this study the methods used were interviews and observation. respondents were given back massage intervention (massage rolling. The intervention was carried out for 3 days with a duration of 5-10 minutes with a sample of 2 people. Results: Based on the results of measuring the volume of breast milk in the two samples at the time of the visit, it showed a very significant increase in breast milk. This is because both clients have been given a rolling massage (back) which can help the hormone oxytocin work in releasing breast milk, accelerating the parasympathetic nerves to convey signals to the back of the brain to stimulate milk production to come out. Conclusion: From the results that the application of back massage (massage rolling) to facilitate breast milk can affect the way hormones work in milk production . Suggestion: It is recommended for further research with more samples and with a longer time regarding the application of back massage (massage rolling) to facilitate breastfeeding in breastfeeding mothers. Keywords: rolling massage, smooth breastfeeding, breastfeeding mothers.